Selected legal problems of online advertising - Nowak-Gruca, Aleksandra (Lexonomica, 2018)
The aim of this article is to analyse the most important issues related to the latest forms of online advertising. In particular, appreciating the importance of online advertising in the development of the information society, the question is then raised about the legal limits of the admissibility of advertising, which is invasive, insistent or contains hidden meaning, inaccessible to the recipient's awareness of content. This issue has been presented from the perspective of European Union (EU) law, in the context of selected directives relevant for online advertising. The problem raised in the article deserves to be developed because we observe a sharp increase in the importance of the Internet, and the online advertising issue has not been the subject of comprehensive regulation in EU law.
Keywords: integrity in advertising; native advertising; online advertising; product placement; unfair competition